Tecnologias associadas à ureia: perdas de N NH3 sob efeito de temperatura e umidade do solo - Siman, Felipe Cunha (2018)
The use of technologies associated with urea granules has been developed with the aim of minimizing N losses in the soil-plant-atmosphere system and increasing the efficiency of nitrogen fertilization through the use of stabilized fertilizers and gradual